# How do you solve -9(-3t + 8) = -13t + 48?

Apr 9, 2018

$t = 3$

#### Explanation:

$- 9 \left(- 3 t + 8\right) = - 13 t + 48$

$\text{Order of Operations - } \textcolor{p u r p \le}{B E D M A S}$

$- 9 \cdot - 3 t - 9 \cdot 8 = - 13 t + 48 , \text{ (Removing bracket)}$

$27 t - 72 = - 13 t + 48 , \text{ (Multiplication, as also } \textcolor{b r o w n}{\left(-\right) \cdot \left(-\right) = +}$

$27 t + 13 t = 48 + 72 , \text{(Bringing like terms together)}$

$- 40 t = 120$

$t = {\cancel{120}}^{\textcolor{red}{3}} / \cancel{40} = 3$

Apr 9, 2018

First expand the brackets.

#### Explanation:

This gives you:

$27 t - 72 = - 13 t + 48$

Then you move the unknowns to one side and the integers to the other:

$27 t + 13 t = 48 + 72$

Then simplify.

$40 t = 120$

$t = 3$

Apr 9, 2018

t=3

#### Explanation:

So here we multiply the number before the bracket with all the numbers in the bracket, let me explain.
$- 9 \left(- 3 t + 8\right) = - 13 t + 48$
$27 t - 72 = - 13 t + 48$
$40 t - 72 = 48$
$40 t = 120$
$\frac{40 t}{40} = \frac{120}{40}$
$t = 3$